Towards a model of community care and support: The deinstitutionalization processes in Spain - Asís Roig, Rafael de; Razo Godinez, Laura Cecilia (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2025)
This work complies the conclusions presented in a series of seminars throughout 2024, following the publication of the EDI Study on Deinstitutionalization Processes and the Transition Towards Personalized and Community-based Support Models. The study was conducted within the framework of the National Deinstitutionalization Strategy in Spain by the IDHPB. These conclusions provide a diagnosis of the state of the care and support model based on institutionalization and segregation, as well as its counterpart: a life chosen within the community, framed by human rights